BELASKASIHAN ALLAH MENGATASI REALITAS KEBERDOSAAN MANUSIA: Refleksi Teologis dan Moralitas Sakramen Tobat - Perbowo, Filipus Bimo (LOGOS, 2025)
This study reflects on the theological and moral significance of the Sacrament of Penance as an expression of God’s mercy in response to the enduring reality of human sinfulness. The main question addressed is: how does the Catholic tradition understand and uphold the Sacrament of Penance as both a personal and communal response to sin in a context marked by moral relativism and diminished awareness of sin? The objective of this paper is to demonstrate that the sacrament is not merely a legal ritual, but a transformative encounter with divine mercy. The method used is theological reflection grounded in Scripture, Magisterium documents, and insights from key theological figures such as Augustine, Thomas Aquinas, Joseph Ratzinger, and Pope Francis. By exploring the dimensions of sin--personal, social, and structural-“this study affirms that genuine conversion is both ethical and relational, requiring personal responsibility and communal restoration. The result shows that the Sacrament of Penance remains essential in forming moral conscience, restoring human dignity, and making God’s redemptive love present in a broken world. Far from being outdated, the sacrament continues to serve as a vital path of healing and reconciliation in the life of the Church today.